2021
DOI: 10.3390/su13063003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Personality and Learning Goal Orientation Preceding the First Employment

Abstract: The purpose of this study is to explore the relation between personality traits and the level of aspiration to acquire new skills and improve one’s competence in the midst of first employment. Although with mixed results, previous studies indicated that personality attributes influence goal orientation, both in the school and work settings. However, there have not been any studies that have specifically analysed this relation in the context preceding the first employment. The results of this research, on a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…The results of Partial Least Squares Structural Equation Modeling (PLS-SEM) path analysis for hypothesis eight on the effect of entrepreneurial leadership and learning orientation on small and medium-sized enterprises (SMEs) growth moderated by prior entrepreneurial exposure found that prior entrepreneurial exposure did not significantly moderate the effect of entrepreneurial leadership and learning orientation on small and medium-sized enterprises (SMEs) growth. Conceptually, although prior entrepreneurial exposure did not significantly moderate the effect of entrepreneurial leadership and learning orientation on SMEs growth could be linked to the position of other scholars that despite the values of entrepreneurial exposure which can come from existing entrepreneurs in the form of role models, shadowing the entrepreneur, having entrepreneurial family members, or prior work experience in an entrepreneurial firm, an entrepreneur past experiences may not signify that the business will flourish (Hsu et al, 2017;Nowinski & Haddoud, 2019) due to factors not excluding entrepreneur personality (Longin et al, 2021;Neneh, 2019). Nevertheless, the positive effect supports the position of scholars that prior entrepreneurship exposure contributes to the acquisition of entrepreneurial knowledge (Malebana & Mothibi, 2023;Miralles et al, 2017), which plays a crucial role in distinguishing successful from unsuccessful entrepreneurs in identifying and exploiting opportunities as well as their ability to innovate (Shi & Weber, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The results of Partial Least Squares Structural Equation Modeling (PLS-SEM) path analysis for hypothesis eight on the effect of entrepreneurial leadership and learning orientation on small and medium-sized enterprises (SMEs) growth moderated by prior entrepreneurial exposure found that prior entrepreneurial exposure did not significantly moderate the effect of entrepreneurial leadership and learning orientation on small and medium-sized enterprises (SMEs) growth. Conceptually, although prior entrepreneurial exposure did not significantly moderate the effect of entrepreneurial leadership and learning orientation on SMEs growth could be linked to the position of other scholars that despite the values of entrepreneurial exposure which can come from existing entrepreneurs in the form of role models, shadowing the entrepreneur, having entrepreneurial family members, or prior work experience in an entrepreneurial firm, an entrepreneur past experiences may not signify that the business will flourish (Hsu et al, 2017;Nowinski & Haddoud, 2019) due to factors not excluding entrepreneur personality (Longin et al, 2021;Neneh, 2019). Nevertheless, the positive effect supports the position of scholars that prior entrepreneurship exposure contributes to the acquisition of entrepreneurial knowledge (Malebana & Mothibi, 2023;Miralles et al, 2017), which plays a crucial role in distinguishing successful from unsuccessful entrepreneurs in identifying and exploiting opportunities as well as their ability to innovate (Shi & Weber, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Many different forms of this distinct type of integration of competence-based and non-competence-based constructs are present in the achievement motivation literature. Illustrative examples Include the following: temperaments (Gray, 1987), namely approach and avoidance temperament, as predictors of achievement goals ; see also Bipp et al, 2017;Bjørnebekk & Diseth, 2021;Lochbaum et al, 2013;Rawlings et al, 2020;Sánchez Rosas, 2015;Scott et al, 2015); attachment dimensions (Fraley & Shaver, 2000), namely anxiety and avoidance dimensions, and attachment security as predictors of achievement goals (Elliot & Reis, 2003; see also Bal & Barušs, 2007;Maltais et al, 2015;McNeill et al, 2015;Or et al, 2015;Özgüngör, 2020;Wang et al, 2018); social motives and needs (Veroff & Veroff, 1980) such as the need for affiliation and social interdependence preferences (Elliot et al, 2016; see also Bardach et al, 2020;Bipp & Dam, 2014;Nie & Liem, 2013;Lee et al, 2020;Pulfrey & Butera, 2016;Won et al, 2018) and Big Five traits (Costa & McCrae, 1985) as predictors of achievement goals (McCabe et al, 2013; see also Bipp et al, 2008;Chen, 2015;Chen & Zhang, 2011;Longin et al, 2021;Miller & Speirs Neumeister, 2017;Payne et al, 2007;Pickett et al, 2019;Zheng et al, 2019); trait autonomy, autonomy support, and felt autonomy (Ryan & Deci, 2019) ...…”
Section: Non-competence-based Constructsmentioning
confidence: 99%